2015
DOI: 10.5152/anatoljcardiol.2015.6532
|View full text |Cite
|
Sign up to set email alerts
|

A review of the fixed dose use of new oral anticoagulants in obese patients: Is it really enough?

Abstract: Obesity is a significant cause of morbidity and mortality, and it is becoming increasingly prevalent worldwide. Altered pharmacodynamics and pharmacokinetics of drugs in obese patients require dose adjustment according to body weight. New oral anticoagulants (NOACs), which are more frequently used for anticoagulation, are recommended to be used at a fixed dose based on data derived from phase 2 and 3 studies. However, the representation of obese patients [>100 kg or a body mass index (BMI) of >30 kg/m2] in sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
(52 reference statements)
1
13
0
1
Order By: Relevance
“…Two recent studies have added to the increasing body of evidence that balanced crystalloid solutions are associated with improved outcomes compared to 0.9% saline for all patients. 2,3 These support existing evidence focusing exclusively on patients with sepsis, indicating better outcomes in patients managed with balanced crystalloids. 4 There are clear limitations to the available evidence and studies vary according to inclusion criteria, design and outcome measurement.…”
Section: Which Crystalloid? Does Fluid Choice Influence Patient Outcosupporting
confidence: 71%
See 1 more Smart Citation
“…Two recent studies have added to the increasing body of evidence that balanced crystalloid solutions are associated with improved outcomes compared to 0.9% saline for all patients. 2,3 These support existing evidence focusing exclusively on patients with sepsis, indicating better outcomes in patients managed with balanced crystalloids. 4 There are clear limitations to the available evidence and studies vary according to inclusion criteria, design and outcome measurement.…”
Section: Which Crystalloid? Does Fluid Choice Influence Patient Outcosupporting
confidence: 71%
“…Results indicated that patients with higher body weights had lower peak concentrations, increased volume of distribution and shorter half-lives of DOACs. 3,4 Although dose adjustment of DOACs in severely obese patients are still not recommended on the product literature, expert guidance suggests avoiding DOACs in patients with a BMI of >40 kg/m 2 , or a weight of >120 kg. 4 If DOACs are used in such patients, they recommend checking drug-specific peak and trough levels and substituting it with a vitamin K antagonist if the levels are below the expected range, rather than adjusting the DOAC dose.…”
Section: Beware Of Thromboembolic Risk In Obese Patients On Direct Ormentioning
confidence: 99%
“…In our dose subgroup analysis, we found that standard dose apixaban and rivaroxaban were associated with a lower risk of stroke/SE compared to warfarin, and standard-dose apixaban and dabigatran were associated with a lower risk of MB compared to warfarin. In addition to this subgroup analysis, some real-world studies have evaluated the effectiveness of fixed-dose NOACs in patients with obesity [28]. While patients with obesity often require the dose adjustment of drugs due to altered pharmacokinetics, the current recommendations for NOAC therapy imply fixed-dose treatment.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However, there is concern about the extrapolation of randomized clinical trials to real-life patients 7 since the reality observed in the idealized clinical trial setting is different from the real clinical practice, where patient characteristics and outcomes differ amongst distinct trials. 8 In fact, although fixed doses of DOACs are defined in the guidelines, dose adjustments are currently recommended in the presence of specific clinical conditions, including renal function, [9][10][11][12][13] age and body weight, 14,15 increased bleeding risk (e.g. gastritis, oesophagitis, gastroesophageal reflux) 16 and concomitantly administration with other drugs that compromise DOACs systemic exposition and pharmacological effects (e.g.…”
Section: Introductionmentioning
confidence: 99%